Mapping knowledge production for managing aquatic food systems: the case of Community Fish Refuges (CFRs) in Cambodia - Baldivieso, Carla; Bonatti, Michelle; de Silva, Sanjiv; Dubois, Mark; Sieber, Stefan (WorldFish, 2023)
This study aims to understand how knowledge creation and application occurs among multiple and diverse actors in support of Community Fish Refuges (CFRs) in Cambodia.